The effect of tracer contact on return to care among adult, "lost to follow‐up" patients living with HIV in Zambia: an instrumental variable analysis. Issue 12 (18th December 2021) - Beres, Laura K.; Mody, Aaloke; Sikombe, Kombatende; Nicholas, Lauren Hersch; Schwartz, Sheree; Eshun‐Wilson, Ingrid; Somwe, Paul; Simbeza, Sandra; Pry, Jake M.; Kaumba, Paul; McGready, John; Holmes, Charles B.; et al.
Abstract: Introduction: Tracing patients lost to follow‐up (LTFU) from HIV care is widely practiced, yet we have little knowledge of its causal effect on care engagement. In a prospective, Zambian cohort, we examined the effect of tracing on return to care within 2 years of LTFU. Methods: We traced a stratified, random sample of LTFU patients who had received HIV care between August 2013 and July 2015. LTFU was defined as a gap of >90 days from last scheduled appointment in the routine electronic medical record. Extracting 2 years of follow‐up visit data through 2017, we identified patients who returned. Using random selection for tracing as an instrumental variable (IV), we used conditional two‐stage least squares regression to estimate the local average treatment effect of tracer contact on return. We examined the observational association between tracer contact and return among patient sub‐groups self‐confirmed as disengaged from care. Results: Of the 24, 164 LTFU patients enumerated, 4380 were randomly selected for tracing and 1158 were contacted by a tracer within a median of 14.8 months post‐loss. IV analysis found that patients contacted by a tracer because they were randomized to tracing were no more likely to return than those not contacted (adjusted risk difference [aRD]: 3%, 95% CI: –2%, 8%, p = 0.23). Observational data showed that among contacted, disengaged patients, the rate of return was higher in the week following tracer contact (IR 5.74, 95% CI: 3.78–8.71) than in the 2 weeks to 1‐month post‐contact (IR 2.28, 95% CI: 1.40–3.72). There was a greater effect of tracing among patients lost for >6 months compared to those contacted within 3 months of loss. Conclusions: Overall, tracer contact did not causally increase LTFU patient return to HIV care, demonstrating the limited impact of tracing in this program, where contact occurred months after patients were LTFU. However, observational data suggest that tracing may speed return among some LTFU patients genuinely out‐of‐care. Further studies may improve tracing effectiveness by examining the mechanisms underlying the impact of tracing on return to care, the effect of tracing at different times‐since‐loss and using more accurate identification of patients who are truly disengaged to target tracing.